Structural-Semantic Characteristics Of Tavtological Phraseologies Of The Russian Language - Klara Mirzaeva, Yorkinoy Khamraeva, Luiza Khalilova, (International Journal of Advanced Science and Technology, 2020)
This article analyzes the qualitative and circumstantial phrase logical units of the Russian language on the basis of lexicographic sources from the point of view of the paradigmatic aspect. Four models of structural-semantic features of the units under study are presented.